Ecotechnnology – Physical and Technical Foundation of Pyrolyses Parameters (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The paper deals with the environmentally safe waste processing problem. The pyrolysis is one of the most prospective among different utilization methods of residuals. For hearing organic mass in the pyrolysis process up to 5500C author recommends to apply high frequency and high intensity electromagnetic fields. It is necessary to analyze relationships between waste electrical parameters and frequency of electromagnetic field to achieve optimal parameter of electromagnetic heating. For this purpose was worked out a device for measuring dielectric permittivity and dielectric losses in the range of electromagnetic frequencies between 0.05 – 50 MHz. The measurements were accomplished on the samplers composed of different quantity of organic and inorganic (dielectrics and conductors) materials. The methodology of calculation optimal physical and technical squares for implementation of suggested technology was applied and experimental data were analyzed. The best parameters of electromagnetic field for pyrolysis of solid wastes is frequency f=1,5 – 4∙106 Hz and electric intensity E=180 – 220 kV/m and E=390 – 40 kV/m for waste of different composition.